Heat transfer enhancement in mixed convection poiseuille flow of nanofluid with gold nanoparticles in the presence of thermal diffusion and chemical reaction - Sidra, Aman; Ilyas, Khan; Mohd Zuki, Salleh; Zulkhibri, Ismail (2018)
Heat transfer enhancement of mixed convection Poiseuille flow of nanofluid with gold nanoparticles are studied. The external pressure gradient and buoyancy force induce mixed convection. Chemical reaction and thermal diffusion are also taken into account. Cylindrical shape gold nanoparticles ( ) AuNP are chosen in kerosene oil (base fluid). The problem is modelled in terms of partial differential equations with suitable boundary conditions. Expressions for velocity and temperature are obtained by using perturbation method. Heat transfer rate is evaluated for gold, magnetite and Alumina nanoparticles for the sake of comparison. Gold nanoparticles are found to have highest heat transfer rate. Graphical results are mapped in order to present a better insight the of the embedded parameters effect on the flow of nanofluid.